1988
DOI: 10.3181/00379727-188-3-rc2
|View full text |Cite
|
Sign up to set email alerts
|

A High-Salt Meal Produces Natriuresis in Humans Without Elevating Plasma Atriopeptin

Abstract: The effects of a high-sodium meal on plasma atrial natriuretic peptide (atriopeptin) and renal sodium excretion were studied in eight normal human subjects. As expected, sodium excretion and urine osmolality increased following the meal. Plasma atriopeptin levels did not increase, however, after the high-sodium meal. In a control experiment, consumption of a low-sodium meal by six of the same subjects did not increase either urinary sodium excretion or plasma atriopeptin concentration. We conclude that the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Our conclusion is further strengthened by the selection of intermeal intervals, between treatment consumption and the measurement of FI and WI, that spanned the times for which acute effects of Na + intake have been reported (Hunt and Pathak 1960;Driver 1988;Saville et al 1988). FI was measured 120 min after treatment consumption in experiment 1 for two reasons.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our conclusion is further strengthened by the selection of intermeal intervals, between treatment consumption and the measurement of FI and WI, that spanned the times for which acute effects of Na + intake have been reported (Hunt and Pathak 1960;Driver 1988;Saville et al 1988). FI was measured 120 min after treatment consumption in experiment 1 for two reasons.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study of healthy adults, ingestion of 2300 mg Na + dissolved in water increased plasma osmolality to the thirst threshold within 30 min (Saville et al 1988), a change that triggers WI (Vokes 1987). On each of the 5 treatment days, participants consumed 1 of 5 tomato beverages, which had 0, 500, 1000, 1500, or 2000 mg of added Na + .…”
Section: Methodsmentioning
confidence: 96%
“…The measurement of plasma atriopeptin only once each day would be unlikely to detect changes in this hormone that might occur transiently after sodium ingestion. Saville and his coworkers 21 attempted to detect postprandial changes by measuring circulating atriopeptin before and after normal human subjects ate a high sodium breakfast containing 100 mmol sodium chloride. On a separate morning several weeks later, the subjects ate a low sodium breakfast that contained the same number of calories but only 4 mmol sodium chloride.…”
Section: Alterations In Dietary Sodiummentioning
confidence: 99%
“…The key observation, however, was that plasma atriopeptin did not increase after either meal. Saville and his colleagues 21 concluded that atriopeptin was not responsible for the natriuresis induced by the high salt meal or for the diuresis induced by the low salt meal.…”
Section: Alterations In Dietary Sodiummentioning
confidence: 99%
“…In contrast, in chronic volume expansion, induced by high dietary sodium intake, no change or a minimum de gree o f increase in plasma A N P has been reported [78,79]. Also, a study using autoimmune rats against A N P demon strated that natriuresis produced by chronic oral salt load ing was comparable to that o f control animals [77], It appears, therefore, that A N P does not play a major role in the Huid homeostasis during chronic, as opposed to acute, volume expansion.…”
Section: Volume Expansionmentioning
confidence: 99%